Non-Clinical In Vitro Evaluation of Antibiotic Resistance Gene-Free Plasmids Encoding Human or Murine IL-12 Intended for First-in-Human Clinical Study - Spela Kos; Masa Bosnjak; Tanja Jesenko; Bostjan Markelc; Urska Kamensek; Katarina Znidar; Urska Matkovic; Andrej Rencelj; Gregor Sersa; Rosana Hudej; Aneja Tuljak; Matjaz Peterka; et al. (MDPI AG, 2021)
Interleukin 12 (IL-12) is a key cytokine that mediates antitumor activity of immune cells. To fulfill its clinical potential, the development is focused on localized delivery systems, such as gene electrotransfer, which can provide localized delivery of IL-12 to the tumor microenvironment. Gene electrotransfer of the plasmid encoding human IL-12 is already in clinical trials in USA, demonstrating positive results in the treatment of melanoma patients. To comply with EU regulatory requirements for clinical application, which recommend the use of antibiotic resistance gene-free plasmids, we constructed and developed the production process for the clinical grade quality antibiotic resistance gene-free plasmid encoding human IL-12 (p21-hIL-12-ORT) and its ortholog encoding murine IL-12 (p21-mIL-12-ORT). To demonstrate the suitability of the p21-hIL-12-ORT or p21-mIL-12-ORT plasmid for the first-in-human clinical trial, the biological activity of the expressed transgene, its level of expression and plasmid copy number were determined in vitro in the human squamous cell carcinoma cell line FaDu and the murine colon carcinoma cell line CT26. The results of the non-clinical evaluation in vitro set the basis for further in vivo testing and evaluation of antitumor activity of therapeutic molecules in murine models as well as provide crucial data for further clinical trials of the constructed antibiotic resistance gene-free plasmid in humans.